Direct Writing of Hydrophobic Sol-Gel Patterns. Issue 1804 (2015) - Banerjee, Derrick A.; Sierros, Konstantinos A.
ABSTRACT: Solution-based fabrication methods have been widely used for depositing uniform functional coatings. These coatings can be utilized in a variety of applications such as optoelectronics, biomedical, and energy. However, such fabrication techniques are not appropriate for directly depositing patterned micro/nano-scale features, which are required in many contact-based applications such as in MEMS. In this work we propose the direct writing of hydrophobic silica-based sol-gel patterns with sustained functionality and their subsequent tribological characterization. Such an approach may be an advantageous alternative to current lithography-based methods due to the relative ease of processing and low material waste. This investigation involves the abrasive wear and frictional analysis of patterned fluorinated silica sol-gel coatings that are directly printed onto glass substrates with a robotically controlled pneumatic nozzle system. Such work sheds light on the tribological properties of lithography-free processed hydrophobic patterns for applications spanning from micromotors to biomedical fluidic devices.